Are the specific and nonspecific ANA staining patterns of Behcet's Disease patients important? - Ilhan, Fulya; Aksoy, Rahime; Tutkak, Huseyin (Elsevier Espana Slu, 2022)
Background: The autoinflammatory character of Behcet's Disease has led researchers to investigate the role of autoantibodies. However, no significant positive result has been reported for autoantibody tests for the disease. Aims: To investigate the specific and nonspecific staining patterns of Behcet's Disease (BD) patients.Methods: 140 patients (87 females, 53 males) with an average of 41.9 +/- 3 years who were being followed up for Behcet's Disease, and a control group consisting of a total of 736 (464 females, 272 males) healthy volunteers made up of blood donors without any disease whose average age was 50.2 +/- 4 years were included in the study. Peripheral venous blood was collected from the patients and the sera were separated. Patient sera were studied by indirect immunofluorescence antibody test (IFA) at a dilution of 1/40 and 1/100. Results: A total of 140 (87 females, 53 males) Behcet's Disease patients and 736 (464 females, 272 males) healthy controls were examined. The rate of ANA positivity was 11.6% in the control group and 10.7% in the Behcet's Disease group. In general, no difference was detected between the patients and the healthy controls in terms of autoantibody positivity (p > 0.05). However, when examined in terms of patterns, the low detection of DFS70 and the observation of centriole staining type patterns in Behc , et's Disease patients was noteworthy (p < 0.05). Conclusion: Autoantibody tests, which hold an important place in classic autoimmune diseases, are not necessary for Behcet's patients, but they should be examined in terms of nonspecific patterns. (c) 2020 Elsevier Espana, S.L.U. and Sociedad Espanola de Reumatologia y Colegio Mexicano de Reumatologia. All rights reserved.
Keywords: ANA staining patterns; Autoantibodies; Behcet's Disease